2014
DOI: 10.1016/j.toxicon.2014.04.009
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the ability of Bellucia dichotoma Cogn. (Melastomataceae) extract to inhibit the local effects of Bothrops atrox venom when pre-incubated and when used according to traditional methods

Abstract: Bellucia dichotoma Cogn. (Melastomataceae) is one of various plant species used in folk medicine in the west of the state of Pará, Brazil, to treat snake bites. Many studies have been carried out to evaluate the effectiveness of anti-snake bite plants, but few of these use the same preparation methods and doses as those traditionally used by the local populations. This study therefore compared inhibition of the main local effects of B. atrox venom (BaV) by aqueous extract of B. dichotoma (AEBd) administered ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…The application of the very popular black-stone has been proven ineffective because insufficiently specific to venom proteins, although the absorbing capacity of some types of these "snake stones" has been observed [11,12]. Regarding any benefit of herbal traditional treatments, extensive research suggested encouraging local effects of many plants [13][14][15][16][17] but never when they are used in the raw manner in which they are used in communities [18].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…The application of the very popular black-stone has been proven ineffective because insufficiently specific to venom proteins, although the absorbing capacity of some types of these "snake stones" has been observed [11,12]. Regarding any benefit of herbal traditional treatments, extensive research suggested encouraging local effects of many plants [13][14][15][16][17] but never when they are used in the raw manner in which they are used in communities [18].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Although scientifically valid and even recommended by WHO for assessing antiophidic antivenoms [ 97 ], this preincubation approach makes a scenario unlikely to be possible in the field, where the medicine would be delivered after the snakebite. In fact, a recent study evaluated the inhibitory action of the medicinal plant Bellucia dichotoma (Melastomataceae) against Bothrops atrox snake venom using different protocols: preincubation, pretreatment, and posttreatment [ 98 ]. The authors observed that while the extract was greatly active when preincubated, this inhibitory activity was drastically reduced or even lost when the extract was injected independently of venom, simulating traditional use.…”
Section: Antivenom Activities Of Extracts Of Medicinal Plants Agaimentioning
confidence: 99%
“…The authors observed that the extract has great amounts of tannins, which are compounds known to precipitate proteins. So, it was concluded that the “pseudo-inhibition” observed after preincubation may be due to the presence of these compounds, suggesting that the preincubation protocol overestimates inhibitory potential of medicinal plants, and for this reason, this kind of approach must be analyzed with caution for estimation of inhibitory potential of medicinal plants [ 13 , 98 ]. In this sense, many recent studies have been done using protocols of pre- and/or posttreatment, to ensure the potentiality of antiophidic plants, and for most of them, positive results have been found [ 96 , 98 102 ].…”
Section: Antivenom Activities Of Extracts Of Medicinal Plants Agaimentioning
confidence: 99%
“…A second possible mechanism is based on the ability of phenolic compounds to chelate metal ions, such as zinc and calcium, which are essential cofactors of enzymatic toxins. [49][50][51] The regions involved in this mechanism of action are usually found between the 5-OH positions and the 4-oxo group, or between the 3′-and 4′-OH hydroxyls of the compounds. [52] However, the property of phenolic compounds enzymatic toxins, [53] resulting in a decrease in their activities.…”
Section: Discussionmentioning
confidence: 99%